Association Between Salivary C-Reactive Protein Levels and Covariates in an Older Adult Population in Malaysia — A Cross-Sectional Study of The MyAgeWell Cohort - Wei-Gene Lim; Wei Ling Lim; Tze Pheng Lau; Yook Chin Chia; Jactty Chew (Progress in Microbes and Molecular Biology, 2025)
Malaysia's aging population faces heightened risks of cardiovascular diseases, cancers, metabolic disorders, and physical and cognitive decline. Inflammatory biomarkers, such as C-reactive protein (CRP), play a key role in age-related ailments. For instance, elevated CRP levels are linked to an increased risk of cardiovascular diseases and cognitive decline. It is of particular interest to investigate CRP levels and their correlation with various factors among older adults to develop potential predictive markers and interventions for age-related diseases. In recent years, salivary samples have become a viable non-invasive alternative approach to studying CRP levels. Hence, this study aims to examine salivary CRP levels and explore the influences of age, ethnicity, gender, body mass index (BMI) and economic status on salivary CRP levels among older adults. The study was registered at ClinicalTrials.gov (NCT06376656) and ethical approval was obtained from the Sunway University Research Ethics Committee (SUREC 2020/039). A total of 382 saliva samples were collected from the older adults (≥ 60 years) through the MyAgeWell cohort for analysis. Various covariates including age, gender, ethnicity, BMI, and economic status were recorded. Salivary CRP levels were measured using ELISA. We observed a median CRP concentration of 0.39 ng/mL (IQR = 0 – 1.36 ng/mL). Correlation analysis shows salivary CRP levels were associated with gender, ethnicity, and BMI (p < 0.05), but not age and economic status. These findings suggest diverse influences on inflammation among Malaysian older adults. In conclusion, this study advances the understanding of salivary CRP levels in healthy older adults, highlighting the complex nature of inflammation in this population and the importance of addressing modifiable risk factors to reduce health disparities.